(untitled) (Medical Forum Monthly, 2024)
Objective: Staphylococcus saprophyticus is a uropathogen frequently isolated from young female outpatients presenting with uncomplicated urinary tract infections.1 Antibiotic resistance in uropathogen is increasing worldwide in out patients as well as hospitalized patients 2 Study design: cross-sectional study. Place and Duration of Study: The urine specimens were obtained from Nephrology, Urology and Gynecology / Obstetric and outpatient departments of JPMC, Karachi for three years. They were processed in the Department of Microbiology, Basic Medical Sciences Institute, Jinnah Postgraduate Medical Centre, Karachi from May 2003 to May 2005. Material and Methods: The proper and necessary records of the patient were maintained, then the samples were processed by the standard methods. Blood agar plates and MacConkey’s agar plates were used for culture. The biochemical tests were done by using different sugar media, TSI, Simon citrate agar, urease, indole and MRVP tests Result: Out of 175 urinary pathogens isolated from female patients complaining from symptoms of UTI, 28 (16%) yielded Saprophyticus predominantly in pure culture and in high counts. In the age group of 18-28 years, this organism was found in 10 (36%), while in the age group of 29-39 years it was found in 8 female patients i.e. it was 28%. Conclusion: Hence it is observed that as the age advances Staph saprophyticus becomes a rare finding so it is not a common organism in elderly males as well as females of all ages. But the sensitivity pattern must be seen to commonly use antimicrobial agents for proper and timely therapy.